Great Powers, The Middle East, and The Cold War (Case Study – Islamic Republic of Iran and Kingdom of Saudi Arabia) - Kodagoda Janaka Ranaweera (CV. Rayyan Dwi Bharata, 2023)
The Middle East is a highly dynamic and unstructured regional system in which power relations are fluid, competitive, and volatile. Inevitably, the fluidity of power and the competition of a regional hegemonic power have invited external intervention. Furthermore, the region’s dynamism not only has exacerbated the subsystem’s fragmentation into sub-regions but also has afforded opportunities for the better-endowed small Arab states to play in the greater game of regional power politics. Due to its geopolitical importance, any inter-and intra-state conflict in the Middle East has the potential not only of destabilizing the region as a whole or upset the regional balance of power but also to affect global stability. For these reasons, the Middle East has been a major center of world affairs; an economically, politically, and culturally sensitive area. The purpose of this analysis is to provide an account of international relations and the concept of power in the contemporary Middle East. To address the question of regional order, attention will focus on the policies of the main actors such as Saudi Arabia, Iran, Turkey, Yemen, the United States, and other non-state actors.